Monitoring Results after 36 Ktonnes of Deep CO2 Injection at the Aquistore CO2 Storage Site, Saskatchewan, Canada. (July 2017) - White, Don; Harris, Kyle; Roach, Lisa; Roberts, Brian; Worth, Kyle; Stork, Anna; Nixon, Christopher; Schmitt, Douglas; Daley, Tom; Samson, Claire
Abstract: The Aquistore CO2 Storage Site is located in southeastern Saskatchewan, Canada. CO2 is injected into a brine-filled sandstone formation at ∼3200 m depth immediately above the Precambrian basement. Sustained injection rates of 400-600 tonnes/day were achieved at the site starting in the fall of 2015 with a total of 88 ktonnes having been injected by the end of September, 2016. Seismic monitoring methods have been employed to track the subsurface CO2 plume and to record any injection-induced seismicity. Passive seismic monitoring is being conducted using two orthogonal arrays of short-period geophones, 3 broadband seismographs, and an array of downhole geophones. No significant injection-related seismicity (Mw > -1) has been detected during the first 17 months of CO2 injection. The first post-injection time-lapse 3D seismic surveys (surface and VSP) were conducted at the site in February, 2016. The VSP data were acquired with a distributed acoustic sensing system using a 2750 m casing-conveyed optical fibre cable in the observation well. 3D seismic modelling of fluid flow simulations in conjunction with seismic repeatability estimates obtained from field data indicate that the time-lapse VSP should be capable of imaging the CO2 plume after a total injection of ∼30 ktonnes. In addition, this first monitor survey tests the ability of surface seismic data acquired with a sparse permanent array to detect or image the CO2 plume after limited injection. Time-lapse logging is being conducted on a regular basis to provide in situ measurement of the change in seismic velocity associated with changes in CO2 saturation.